Biochemical characterization of a low molecular weight aspartic protease inhibitor from thermo-tolerant bacillus licheniformis: kinetic interactions with pepsin - Kumar, Ajit; Rao, Mala (Biochimica et Biophysica Acta-General Subjects, 2006)
The present article reports a low molecular weight aspartic protease inhibitor, API, from a newly isolated thermo-tolerant Bacillus licheniformis. The inhibitor was purified to homogeneity as shown by rp-HPLC and SDS-PAGE. API is found to be stable over a broad pH range of 2-11 and at temperature 90 degrees C for 2 1/2 h. It has a Mr (relative molecular mass) of 1363 Da as shown by MALDI-TOF spectra and 1358 Da as analyzed by SDS-PAGE The amino acid analysis of the peptide shows the presence of 12 amino acid residues having Mr of 1425Da. The secondary structure of API as analyzed by the CD spectra showed 7% alpha-helix, 49% beta-sheet and 44% aperiodic structure. The Kinetic studies of Pepsin-API interactions reveal that API is a slow-tight binding competitive inhibitor with the IC(50) and K(i) values 4.0nM and (3.83 nM - 5.31 nM) respectively. The overall inhibition constant K(i)* value is 0.107 +/- 0.015 nM. The progress curves are time-dependent and consistent with slow-tight binding inhibition: E+I reversible arrow (k(4), k(5)) EI reversible arrow (k(6), k(7)) EI*. Rate constant k(6) = 2.73 +/- 0.32 s(-1) reveals a fast isomerization of enzyme-inhibitor complex and very slow dissociation as proved by k(7)=0.068 +/- 0.009s(-1). The Rate constants from the intrinsic tryptophanyl fluorescence data is in agreement with those obtained from the kinetic analysis; therefore, the induced conformational changes were correlated to the isomerization of EI to EI*. (c) 2006 Elsevier B.V. Ail rights reserved.
Keywords: Aspartic protease inhibitor; Bacillus licheniformis; enzyme kinetic; Pepsin; Slow-tight binding inhibition

Conformation and microenvironment of the active site of a low molecular weight 1,4-beta-D-glucan glucanohydrolase from an alkalothermophilic thermomonospora sp.: involvement of lysine and cysteine residues - Jagtap, Sharmili; Rao, Mala (Biochemical and Biophysical Research Communications, 2006)
Conformation and microenvironment at the active site of 1,4-beta-D-glucan glucanohydrolase was probed with fluorescent chemo-affinity labeling using o-phthalaldehyde. OPTA has been known to form a fluorescent isoindole derivative by cross-linking the proximal thiol and amino groups of cysteine and lysine. Modification of lysine of the enzyme by TNBS and of cysteine residue by PHMB abolished the ability of the enzyme to form an isoindole derivative with OPTA. Kinetic analysis of the TNBS and PHMB-modified enzyme suggested the presence of essential lysine and cysteine residues, respectively, at the active site of the enzyme. The substrate protection of the enzyme with carboxymethylcellulose (CMC) confirmed the involvement of lysine and cysteine residues in the active site of the enzyme. Multiple sequence alignment of peptides obtained by tryptic digestion of the enzyme showed cysteine is one of the conserved amino acids corroborating the chemical modification studies. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: 1; 4-beta-D-glucan glucanohydrolase; active site microenvironment; Cysteine; lysine; OPTA; PHMB; Thermomonospora sp.; TNBS

Preparation and characterization of urea-formaldehyde-pepsin bioconjugate: a new biocatalyst system - Vinod, V. P.; Shinde, Sudhirkumar; D'Britto, Virginia; Shukla, P. G.; Rao, Mala (Biotechnology Progress, 2006)
This study describes the synthesis of urea formaldehyde (UF) microspheres by a dispersion polycondensation polymerization method. These microspheres with proper F/U molar ratio can provide highly reactive groups, capable of further condensation with the amino acid residues of enzyme/proteins. Presence of methylols groups in UF microspheres was confirmed by C-13 NMR study. Pepsin, a proteolytic enzyme, was immobilized on the UF microspheres to form bioconjugate system. As compared to the free enzyme in solution, the pepsin in the bioconjugate system exhibited significantly enhanced pH and temperature stability. The urea-formaldehydepepsin bioconjugate system also exhibited excellent proteolytic activity over eight successive reuse cycles with more than 50% of initial activity. A highlight of this new biocatalyst is the ease with which separation of this biocatalyst from the reaction medium may be achieved by mild centrifugation.

Application of cellulases from an alkalothermophilic thermomonospora sp in biopolishing of denims - Anish, Ramakrishnan; Rahman, Mohammad Safikur; Rao, Mala (Biotechnology and Bioengineering, 2007)
Use of cellulase for denim washing is a standard eco-friendly technique to achieve desirable appearance and softness for cotton fabrics and denims. But enzymatic washing of denim till date involved acid cellulase (Trichoderma reesei) and neutral cellulase (Humicola isolens) the use of which has a drawback of backstaining of the indigo dye on to the fabric. Though it has been suggested that pH is a major factor in controlling backstaining there are no reports on use of cellulase under alkaline conditions for denim washing. In this study for the first time an alkali stable endoglucanase from alkalothermophilic Thermomonospora sp. (T-EG) has been used for denim biofinishing under alkaline conditions. T-EG is effective in removing hairiness with negligible weight loss and imparting softness to the fabric. Higher abrasive reactivity with lower backstaining was a preferred property for denim biofinishing exhibited by T-EG. The activities were comparable to acid and neutral cellulases that are being regularly used. The enzyme was also effective under non-buffering conditions which is an added advantage for use in textile industry. A probable mechanism of enzymatic finishing of cotton fabric has been represented based on the unique properties of T-EG.
Keywords: alkaline conditions; biopolishing; Cellulase; denim; Thermomonospora sp

Bacterial enzyme mediated biosynthesis of gold nanoparticles - Bharde, Atul A.; Kulkarni, Aarohi; Rao, Mala; Prabhune, Asmita; Sastry, Murali (Journal of Nanoscience and Nanotechnology, 2007)
Development of synthesis methods for anisotropic metal nanoparticles is of considerable interest due to their remarkable optoelectronic properties. Various shapes ranging from rods to cubes to tetrapods and prisms may be obtained by chemical methods. Here we show that anisotropic gold nanoparticles can be synthesized biologically by the bacterium Actinobacter spp. when challenged with gold chloride in the presence of Bovine serum albumin (BSA). We also observed that synthesis of gold nanoparticles occur with simultaneous induction of the protease enzyme secreted by the bacterium in the presence of BSA. The presence of BSA helps to enhance the rate of gold nanoparticles biosynthesis and may also impart some shape control. Controlling simple experimental conditions like incubation temperature and presence or absence of oxygen have drastic effect on the reaction rate and the morphology of the particles. Various assay experiments show that the presence of enzyme protease can act as a reducing as well as shape directing agent.
Keywords: Biosynthesis; bovine serum; gold nanoparticles

Biochemical characterization of a novel beta-1-3, 1-4 glucan 4-glucanohydrolase from thermomonospora sp having a single active site for lichenan and xylan - Anish, Ramakrishnan; Rao, Mala (Biochimie, 2007)
A bifunctional high molecular weight (Mr, 64,500 Da) beta-1-3, 1-4 glucan 4-glucanohydrolase was purified to homogeneity from Thermomonospora sp., exhibiting activity towards lichenan and xylan. A kinetic method was used to analyze the active site that hydrolyzes lichenan and xylan. The experimental data was in agreement with the theoretical values calculated for a single active site. Probing the conformation and microenvironment at active site of the enzyme by fluorescent chemo-affinity label, OPTA resulted in the formation of an isoindole derivative with complete inactivation of the enzyme to hydrolyse both lichenan and xylan confirmed the results of kinetic method. OPTA forms an isoindole derivative by cross-linking the proximal thiol and amino groups. The modification of cysteine and lysine residues by DTNB and TNBS respectively abolished the ability of the enzyme to form an isoindole derivative with OPTA, indicating the participation of cysteine and lysine in the formation of isoindole complex. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: 1-4 glucan 4-glucanohydrolase; beta-1-3; bifunctional; O-phthaialdehyde; single active site; Thermomonospora sp.; Xylanase

Biochemical characterization of an aspartic protease from vigna radiata: kinetic interactions with the classical inhibitor pepstatin implicating a tight binding mechanism - Kulkarni, Aarohi; Rao, Mala (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2007)
{Aspartic proteases are the focus of recent research interest in understanding the physiological importance of this class of enzymes in plants. This is the first report of an aspartic protease from the seeds of Vigna radiata. The aspartic protease was purified to homogeneity by fractional ammonium sulfate precipitation and pepstatin-A agarose affinity column. It was found to have a molecular weight of 67,406 Da by gel filtration chromatography. SDS-PAGE analysis revealed the presence of a heterodimer with subunits of molecular weights of 44,024 and 23,349 Da respectively. The enzyme was pH stable with the amino acid analysis confirming the molecular weight of the protein. The substrate cleavage site as analyzed by using the synthetic substrate was found to be the Phe-Tyr bond. The kinetic interactions of the enzyme were studied with the universal inhibitor, pepstatin A. This is the first report on the interactions of a plant aspartic protease with pepstatin-A, an inhibitor from a microbial source. A competitive one-step mechanism of binding is observed. The progress curves are time-dependent and consistent with tight binding inhibition. The K(i) value of the reversible complex of pepstatin with the enzyme was 0.87 mu M whereas the overall inhibition constant K(i)*
Keywords: ant colony; global optimization; metaheuristics; multimodal continuous functions; particle swarm optimization

Encapsulation of endoglucanase using a biopolymer Gum arabic for its controlled release - Ramakrishnan, Anish; Pandit, Nilesh; Badgujar, Mahesh; Bhaskar, C.; Rao, Mala (Bioresource Technology, 2007)
{Gum Arabic, a biodegradable natural polymer was used as a matrix to encapsulate endoglucanase from Thermomonospora sp. The modified enzyme retained complete biocatalytic activity and exhibited a shift in the optimum temperature [
Keywords: Enzyme catalysis; OPTA; Thermomonospora sp.; Xylanase

Glycine-assisted enhancement of 1,4-beta-D-xylan xylanohydrolase activity at alkaline pH with a pH optimum shift - Vathipadiekal, Vinod; Verma, Anamika; Rao, Mala (Biological Chemistry, 2007)
This is the first report describing the enhancement of xylanase activity by the neutral amino acid glycine. Xylanase activity is increased seven-fold at alkaline pH in the presence of glycine and its pH optimum is shifted from pH 7 to 8 without using any protein engineering techniques. Analysis of the steady-state kinetics revealed that glycine in the reaction mixture increases the K-m and k(cat) values of the enzyme. Chemoaffinity labeling and studies using glycine esters indicate an involvement of the carboxylate ion of glycine in enhancing xylanase catalytic activity. A novel possible mechanism for the glycine-assisted catalytic action of xylanase is proposed.
Keywords: Enzyme catalysis; OPTA; Thermomonospora sp.; Xylanase

pH Induced structural alterations in an aspartic protease from Vigna radiata indicating an alkali induced molten globule state - Kulkarni, Aarohi; Gaikwad, Sushama M.; Rao, Mala (International Journal of Biological Macromolecules, 2008)
pH-dependent transitions in secondary and tertiary structure are described for a plant aspartic protease from Vigna radiata. The enzyme was pH stable with pH optima of 3.0. The Lineweaver Burk analysis at various pH yielded pK(a) values of 3.3 and 4.29 indicating acidic amino acids at the active site of the enzyme. The structural changes exemplified compact secondary structure collapsed tertiary structure and exposure of hydrophobic patches at pH 10. The changes at pH 10 are typical of a molten globule state. This alkali induced molten globule is novel since acid induced molten globule state is more reported. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Alkali induced molten globule; Plant aspartic protease; Structural transitions

Differential elicitation of an aspartic protease inhibitor: regulation of endogenous protease and initial events in germination in seeds of vigna radiata - Kulkarni, Aarohi; Rao, Mala (Peptides, 2009)
Plant aspartic proteases are of recent origin with their physiological significance in crucial processes emerging. Reports on the significance of aspartic protease inhibitors and their endogenous proteases in seeds of plants are scanty. This paper reports the purification of an aspartic protease inhibitor from the seeds of Vigna radiata, its control of the endogenous aspartic protease and their subsequent role in the early germination events. The role of the aspartic protease inhibitor and the enzyme in initial stages of germination of V. radiata has been tracked by differential timed expression and germination assays. The expression pattern revealed maximum expression of the inhibitor in the dormant seeds while the enzyme was predominant in the germinating seeds. Their expression patterns and interactions indicate their significance in initiation of germination. The expression of other classes of proteases was monitored during germination and a model predicting the events occurring during proteolysis of the storage protein in germination is hypothesized. The inhibitor was a linear, hydrophobic, pH stable and thermostable peptide with molecular weight of 1660 Da. The purified inhibitor showed a pI of 4.36 with the sequence as AEIYN KDGNK LDLYG. The inhibitor was found to be stable in a broad range of pH from 2 to 10 with an optimum of 3.0. The half-life of VrAPI at 100 degrees C was 30 min whereas the maximum activity was observed at 37 degrees C. The initial kinetic analysis of the inhibitor against the enclogenous protease showed an IC50 value of 11 nM while the value of the inhibition rate constant K-i was 34 x 10(-9) M. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Aspartic protease; Plant proteases; Protease inhibitors; Vigna radiata

Fluorescence study on interactions of alpha-crystallin with the molten globule state of 1, 4-beta-D-glucan glucanohydrolase from thermomonospora sp induced by guanidine hydrochloride - Jagtap, Sharmili; Rao, Mala (Journal of Fluorescence, 2009)
In this paper, the interaction between alpha- crystallin and molten globule structure of 1,4-beta-D-Glucan Glucohydrolase (TSC) from an alkalothermophilic Thermomonospora sp. was investigated mainly by fluorescence quenching spectra, circular dichroism and three dimensional fluorescence spectra under simulative physiological conditions. Denaturation studies using GdnCl indicated that TSC folds through a partially folded state that resembles molten globule at 1.8 M GdnCl. The chaperone activity of alpha- crystallin was employed to study refolding of TSC. Here we studied the refolding of GdnCl denatured TSC from its molten globule state (TSC-m complex) in the presence and absence of alpha-crystallin to elucidate the molecular mechanism of chaperone-mediated in vitro folding. Our results, based on intrinsic tryptophan fluorescence and ANS binding studies, suggest that alpha-crystallin formed a complex with a putative intermediate molten globule - like intermediate in the refolding pathway of TSC. Reconstitution of the active TSC was observed on cooling the alpha-crystallin aEuro cent TSC -m complex to 4A degrees C. Addition of alpha-crystallin to the molten globule - like intermediate of TSC (TSC-m complex) complex initiated the refolding of TSC with 69 % recovery of the biological activity of the enzyme.
Keywords: ANS; Cellulase; Guanidine hydrochloride; Protein folding

Hydrolysis of cellulose derived from steam exploded bagasse by penicillium cellulases: comparison with commercial cellulase - Singh, Rajkumar; Varma, Anjanikumar; Laxman, Ryali Seeta; Rao, Mala (Bioresource Technology, 2009)
A complete cellulase from Penicillium pinophilum was evaluated for the hydrolysis of a-cellulose derived from steam exploded sugarcane bagasse and other cellulosic substrates. alpha-Cellulose at 1% substrate concentration was completely hydrolyzed by Penicillium cellulase within 3 h wherein at 10% the hydrolysis was 100% within 24 h with an enzyme loading of 10 FPU/g. The hydrolysate yielded glucose as major end product as analyzed by HPLC. Under similar conditions, hydrolysis of Sigmacell (microcrystalline cellulose), CP-123 (pulverized cellulose powder) and ball milled Solka Floc were 42%, 56% and 52%, respectively. Further the hydrolysis performance of Penicillium sp. cellulase is compared with Trichoderma reesei cellulase (Accellerase (TM) 1000) from Genencore. The kinetics of hydrolysis with respect to enzyme and substrate concentration will be presented. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Accellerase (TM) 1000; Enzymatic hydrolysis; High beta-glucosidase; Penicillium cellulase; Sugarcane bagasse

Biocatalytic approach for the utilization of hemicellulose for ethanol production from agricultural residue using thermostable xylanase and thermotolerant yeast - Menon, Vishnu; Prakash, Gyan; Prabhune, Asmita; Rao, Mala (Bioresource Technology, 2010)
A hydrolysis of 62% and 50% for OSX (Oat spelt xylan) and WBH (Wheat bran hemicellulose) were obtained in 36 h and 48 h using Accellerase(TM) 1000 at 50 degrees C wherein thermostable xylanase from alkalothermophilic Thermomonospora sp. yielded 67% (OSX) in 3 h and 58% (WBH) in 24 h at 60 degrees C, favouring a reduction in process time and enzyme dosage. The rate of hydrolysis with thermostable xylanase was increased by 20% with the addition of nonionic surfactant tween 80 or biosurfactant sophorolipid. The simultaneous saccharification and fermentation (SSF) of OSX and WBH using thermostable xylanase and D. hansenii in batch cultures produced 9.1 g/L and 9.5 g/L of ethanol, respectively and had a shorter overall process time than the separate hydrolysis and fermentation (SHF). The immobilized yeast cells in Ca-alginate matrix produced ethanol with a yield of 0.46 g/g from hemicellulosic hydrolysates and were reused six times with 100% fermentation efficiency. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Biosurfactant; Ethanol; Hemicellulose; Thermostable xylanase; Thermotolerant yeast

Enzymatic hydrolysis and ethanol production using xyloglucanase and debaromyces hansenii from tamarind kernel powder: galactoxyloglucan predominant hemicellulose - Menon, Vishnu; Prakash, Gyan; Rao, Mala (Journal of Biotechnology, 2010)
The hydrolysis and ethanol production from tamarind kernel powder (TKP), a rich source of galactoxyloglucan (GXG) was investigated for the first time using xyloglucanase and thermotolerant Debaromyces hansenii. The acid hydrolysis of TKP with 2N H(2)SO(4) at 120 degrees C for 30 min yielded an overall saccharification of 94% based on the total available carbohydrate content and further fermentation at 40 degrees C with thermotolerant D hansenii produced an ethanol yield of 0.35 g/g. A maximum hydrolysis of 55 and 78% for GXG was obtained in 48 h at 50 degrees C using Thermomonospora xyloglucanase (TXy) and accellerase (TM) 1000, respectively. The synergistic effect of beta-galactosidase and xyloglucanase was demonstrated by the exogenous addition of beta-galactosidase to TXy which improved the overall hydrolysis of GXG by 30%. The rate of hydrolysis of GXG with TXy and accellerase was increased by 15-20% in the presence of chemical surfactants (tween 80 and toluene) or protein additive (BSA). The fermentation of enzymatic hydrolysates of GXG by TXy and accellerase with free cells at 40 degrees C produced an ethanol yield of 0.39 and 0.41 g/g whereas with immobilized cells produced 0.45 and 0.43 g/g, respectively, with a theoretical conversion efficiencies of 78-88%. The immobilized yeast cells were reused six times at 40 degrees C with 100% fermentation efficiency. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ethanol; Galactoxyloglucan; Hydrolysis; Tamarind kernel powder; Thermotolerant yeast; Xyloglucanase

Molecular cloning, over expression, and activity studies of a peptidic HIV-1 protease inhibitor: designed synthetic gene to functional recombinant peptide - Vathipadiekal, Vinod; Umasankar, Perunthottathu K.; Patole, Milind S.; Rao, Mala (Peptides, 2010)
The aspartic protease inhibitor (ATBI) purified from a Bacillus sp. is a potent inhibitor of several proteases including recombinant HIV-1 protease, pepsin, and fungal aspartic protease. In this study, we report the cloning, and over expression of a synthetic gene coding for ATBI in Escherichia coli and establish a purification Protocol. The ATBI molecule consists of eleven amino acids and is peptidic in nature. We used the peptide sequence data of ATBI to synthesize complementary oligonucleotides, which were annealed and subsequently cloned in-frame with the gene for glutathione-S-transferase (GST). The expression of the resulting fusion protein was induced in E. coli BL21-A1 cells using arabinose. The recombinant peptide was Purified using a reduced glutathione column, and cleaved with Factor Xa to remove the GST tag. The resultant product was further purified to homogeneity using RP-HPLC. Mass spectroscopy analysis revealed that the purified peptide had a molecular weight of 1186 Da which matches the theoretical molecular weight of the amino acids present in the synthetic gene. The recombinant peptide was found to be active in vitro against HIV-1 protease, pepsin, and fungal aspartic protease. The protocol described in this study may be used to clone pharmaceutically important peptide molecules. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Gateway cloning; HIV-1 protease; inhibitor; Proteases; Synthetic gene

Novel bifunctional peptidic aspartic protease inhibitor inhibits chitinase A from Serratia marcescens: kinetic analysis of inhibition and binding affinity - Kumar, Ajit; Rao, Mala (Biochimica Et Biophysica Acta-General Subjects, 2010)
Background: Chitinase inhibitors have chemotherapeutic potential as fungicides, pesticides and antiasthmatics. The majority of chitinase inhibitors reported are natural products like argifin, argifin linear fragments, argadin, allosamidin and disulfide-cyclized peptides. Here, we report a novel peptidic inhibitor API (Aspartic Protease Inhibitor), isolated from Bacillus licheniforrnis that inhibits chitinase A (ChiA) from Serratia marcescens. Methods: The binding affinity of API with ChiA and type of inhibition was determined by the inhibition kinetics assays. Fluorescence and CD spectroscopic analysis and chemical modification of API with different affinity reagents elucidated the mechanism of binding of API with ChiA. Results and conclusions: The peptide has an amino acid sequence N-Ile(1)-Cys(2)-Glu(3)-Ala(4)-Glu(5)-His(6)-Lys(7)-Trp(8)-Gly(9)-Asp(10) -Tyr(11)-Leu(12)-Asp(13)-C. The ChiA-API kinetic interactions reveal noncompetitive, irreversible and tight binding nature of API with I-50= 600 nM and K-i = 510 nM in the presence of chromogenic substrate pnitrophenyl-N,N'-diacetyl-beta-chitobioside[p-NP-(GIcNAc)(2)]. The inhibition progress curves show a two-step slow tight binding inhibition mechanism with the rate constant k(5) = 8.7 +/- 1 x 10(-3) s(-1) and k(6) = 7.3 +/- 0.6 x 10(-5) s(-1). CD-spectra and tryptophanyl fluorescence analysis of ChiA incubated with increasing API concentrations confirms conformational changes in enzyme structure which may be due to irreversible denaturation of enzyme upon binding of API. Chemical modifications by WRK abolished the anti-chitinase activity of API and revealed the involvement of carboxyl groups in the enzyme inactivation. Abolished isoindole fluorescence of OPTA-labeled ChiA demonstrates the irreversible denaturation of ChiA upon incubation with API for prolonged time and distortion of active site of the enzyme. General significance: The data provide useful information that could lead to the generation of drug-like, natural product-based chitinase inhibitors. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Aspartic protease inhibitor; Bacillus licheniformis; Chitinase A; Enzyme kinetics; Slow tight binding inhibition

Production of single cell protein, essential amino acids, and xylanase by penicillium janthinellum - Rao, Mala; Varma, Anjanikumar; Deshmukh, Sumedha S. (Bioresources, 2010)
Microbial biomass having 46% crude protein content and enriched with essential amino acids as well as extracellular xylanase activity (100-150 IU/ml) was produced by an efficient fungal strain, Penicillium janthinellum (NCIM St-F-3b). Optimization studies for maximum xylanase and biomass production showed that the fungus required a simple medium containing bagasse hemicellulose as carbon source and ammonium sulphate as the nitrogen source. Therefore bagasse, which is a waste product of the sugar industry, can be efficiently used in microbioal biomass protein preparation for animal feed.
Keywords: Bagasse hydrolysate; Crude protein; Microbial biomass production; Penicillium janthinellum; Xylanase

Bioethanol production from renewable polymer lichenan using lichenase from an alkalothermophilic thermomonospora sp and thermotolerant yeast - Menon, Vishnu; Divate, Rupesh; Rao, Mala (Fuel Processing Technology, 2011)
Biomass feedstocks available decentrally will be more commodious for localized biorefinery approach than the exhaustive large scale and centralized plants driven by cost intensive technology. Lichen is present in a wide range of habitats in a distributed manner. A maximum hydrolysis of 73%-76% for lichenan from Cetraria islandica, Usnea barbata and Parmelia sp. were obtained in 24 h using lichenase from an alkalothermophilic Thermomonospora sp. wherein the hydrolysis was 100% with commercial enzyme Accellerase (TM) 1000. The synergistic role of beta-glucosidase in lichenan hydrolysis was demonstrated by the exogenous addition of beta-glucosidase to Thermomonospora lichenase which resulted in complete hydrolysis. The hydrolysates of lichenan obtained using Accellerase or a cocktail of Thermomonospora lichenase and beta-glucosidase when fermented with free cells of Saccharomyces at 40 degrees C produced an ethanol yield of 0.45 g/g-0.48 g/g with theoretical conversion efficiencies of 93%-96%. The Ca-alginate immobilized yeast cells were reused eight times at 40 degrees C with 100% fermentation efficiency. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ethanol; Hydrolysis; Lichenan; Lichenase; Synergism; Thermotolerant yeast

Microbial production of xylitol from D-xylose and sugarcane bagasse hemicellulose using newly isolated thermotolerant yeast Debaryomyces hansenii - Prakash, Gyan; Varma, Anjanikumar; Prabhune, Asmita; Shouche, Yogesh; Rao, Mala (Bioresource Technology, 2011)
A thermotolerant yeast capable of fermenting xylose to xylitol at 40 C was isolated and identified as a strain of Debaryomyces hansenii by ITS sequencing. This paper reports the production of xylitol from D-xylose and sugarcane bagasse hemicellulose by free and Ca-alginate immobilized cells of D. hansenii. The efficiency of free and immobilized cells were compared for xylitol production from D-xylose and hemicellulose in batch culture at 40 degrees C. The maximum xylitol produced by free cells was 68.6 g/L from 100 g/L of xylose, with a yield of 0.76 g/g and volumetric productivity 0.44 g/L/h. The yield of xylitol and volumetric productivity were 0.69 g/g and 0.28 g/L/h respectively from hemicellulosic hydrolysate of sugarcane bagasse after detoxification with activated charcoal and ion exchange resins. The Ca-alginate immobilized D. hansenii cells produced 73.8 g of xylitol from 100 g/L of xylose with a yield of 0.82 g/g and volumetric productivity of 0.46 g/L/h and were reused for five batches with steady bioconversion rates and yields. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Immobilization; Sugarcane bagasse hemicellulose; Thermotolerant Debaryomyces hansenii; xylitol; Xylose

Purification and characterization of an alkaline protease by a new strain of Beauveria sp - Shankar, Shiv; Rao, Mala; Laxman, Ryali Seeta (Process Biochemistry, 2011)
A fungal culture isolated from animal dung was identified as a new strain of Beauveria sp MTCC 5184 based on 18S rDNA and ITS nucleotide sequence homology. The fungal isolate secretes alkaline protease active at pH 9 and 50 degrees C. The alkaline protease from Beauveria sp (BAP) was purified to homogeneity with 10.2-folds increase in specific activity and 38.6% recovery. The molecular mass and isoelectric point of the protease were found to be 29 kDa and 9.3, respectively. The N-terminal sequence of the BAP showed only partial homology with subtilisin like proteases from other fungi. The enzyme was stable up to 40 degrees C and pH 3-11. The protease was inhibited by Cd(2+), Hg(2+) and Mn(2+). The activity was totally lost in the presence of 1 mM PMSF suggesting it to be a serine protease. The protease showed maximum activity with casein followed by haemoglobin and BSA. The purified protease is able to separate the endothelial cells and can be used in animal cell culture. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Alkaline Protease; Animal cell culture; Beauveria sp; Sequence homology

Biochemical characterization of a novel thermostable xyloglucanase from an alkalothermophilic thermomonospora sp. - Pol, Dipali; Menon, Vishnu; Rao, Mala (Extremophiles, 2012)
Xyloglucanase from an extracellular culture filtrate of alkalothermophilic Thermomonospora sp. was purified to homogeneity with a molecular weight of 144 kDa as determined by SDS-PAGE and exhibited specificity towards xyloglucan with apparent K (m) of 1.67 mg/ml. The enzyme was active at a broad range of pH (5-8) and temperatures (40-80A degrees C). The optimum pH and temperature were 7 and 70A degrees C, respectively. The enzyme retained 100% activity at 50A degrees C for 60 h with half-lives of 14 h, 6 h and 7 min at 60, 70 and 80A degrees C, respectively. The kinetics of thermal denaturation revealed that the inactivation at 80A degrees C is due to unfolding of the enzyme as evidenced by the distinct red shift in the wavelength maximum of the fluorescence profile. Xyloglucanase activity was positively modulated in the presence of Zn2+, K+, cysteine, beta-mercaptoethanol and polyols. Thermostability was enhanced in the presence of additives (polyols and glycine) at 80A degrees C. A hydrolysis of 55% for galactoxyloglucan (GXG) from tamarind kernel powder (TKP) was obtained in 12 h at 60A degrees C and 6 h at 70A degrees C using thermostable xyloglucanases, favouring a reduction in process time and enzyme dosage. The enzyme was stable in the presence of commercial detergents (Ariel), indicating its potential as an additive to laundry detergents.
Keywords: Alkalothermophilic Thermomonospora sp.; Biotechnological applications; Purification; Thermostable; Xyloglucanase

Effect of alkali pretreatment on the structural properties and enzymatic hydrolysis of corn cob - Sahare, Padmavati; Singh, Rajkumar; Laxman, Ryali Seeta; Rao, Mala (Applied Biochemistry and Biotechnology, 2012)
An effective alkali pretreatment which affects the structural properties of cellulose (corn cob) has been studied. The pretreatment of corn cob was carried out with different combinations of alkali at varying temperatures. The most effective pretreatment of corn cob was achieved with 1 % alkali at 50 A degrees C in 4 h. The crystallinity index (CrI) and specific surface area (SSA) of untreated corn cob was 39 % and 0.52 m(2)/g wherein after alkali pretreatment CrI decreased to 15 % and SSA increased to 3.32 m(2)/g. The fungal organism was identified as Penicillium pinophilum on the basis of ITS sequence. At 5 % substrate concentration using a complete cellulase from Penicillium pinophilum the hydrolysis of untreated corn cob with 5, 10 and 20 FPU/g enzyme loadings were 11 %, 13 % and 16 %, whereas after alkali treatment the hydrolysis increased to 78 %, 90 % and 100 %, respectively. Further hydrolytic potential of commercial cellulases viz. Accellerase (TM) 1,000, Palkofeel-30 and Palkocel-40 were investigated under similar conditions.
Keywords: Corn cob; Crystallinity index; Enzymatic hydrolysis; Penicillium pinophilum; Specific surface area

Inhibition of xyloglucanase from an alkalothermophilic thermomonospora sp by a peptidic aspartic protease inhibitor from Penicillium sp VM24 - Menon, Vishnu; Rao, Mala (Bioresource Technology, 2012)
A bifunctional inhibitor from Penicilliurn sp VM24 causing inactivation of xyloglucanase from Thermomonospora sp and an aspartic protease from Aspergillus saitoi was identified. Steady state kinetics studies of xyloglucanase and the inhibitor revealed an irreversible, non-competitive, two-step inhibition mechanism with IC50 and K-i; values of 780 and 500 nM respectively. The interaction of o-phthalaldehyde (OPTA)-labeled xyloglucanase with the inhibitor revealed that the inhibitor binds to the active site of the enzyme. Far- and near-UV spectrophotometric analysis suggests that the conformational changes induced in xyloglucanase by the inhibitor may be due to irreversible denaturation of enzyme. The bifunctional inhibitor may have potential as a biocontrol agent for the protection of plants against phytopathogenic fungi. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aspartic protease; Bifunctional inhibitor; Biocontrol agent; Inactivation mechanism; Xyloglucanase

Low-molecular-mass aspartic protease inhibitor from a novel penicillium sp.: implications in combating fungal infections - Menon, Vishnu; Rao, Mala (Microbiology-SGM, 2012)
A low-molecular-mass aspartic protease inhibitor was isolated from a novel Penicillium sp. The inhibitor was purified to homogeneity, as shown by reversed-phase HPLC and SDS-PAGE. The M-r of the inhibitor was 1585 and the amino acid composition showed the presence of D, D, D, E, A, K, L, Y, H, I and W residues. The steady-state kinetic interactions of Aspergillus saitoi aspartic protease with the inhibitor revealed the reversible, competitive, time-dependent tight-binding nature of the inhibitor, with IC50 and K-i values of 1.8 and 0.85 mu M, respectively. Fluorescence spectroscopy and circular dichroism analysis showed that inactivation of the enzyme was due to binding of the inhibitor to the active site. The inhibitor was found to inhibit mycelial growth and spore germination of Aspergillus fumigatus and Aspergillus niger in vitro with MIC values of 1.65 and 0.30 mu g ml(-1), respectively. This study will potentially open the way towards the development of a tight-binding peptidic inhibitor against fungal aspartic proteases to combat human fungal infections.

Production, purification, and characterization of a beta-glucosidase of penicillium funiculosum NCL1 - Ramani, Gurusamy; Meera, Balasubramanian; Vanitha, Chinnathambi; Rao, Mala; Gunasekaran, Paramasamy (Applied Biochemistry and Biotechnology, 2012)
Penicillium funiculosum NCL1, a filamentous fungus, produced significantly higher levels of beta-glucosidase. The effect of initial pH, incubation temperature, and different carbon sources on extracellular beta-glucosidase production was studied in submerged fermentation. At 30 A degrees C with initial pH 5.0, enzyme production was increased by 48-fold upon induction with paper mill waste, as compared to commercial cellulose powder. In zymogram analysis, four isoforms of beta-glucosidases were observed with wheat bran whereas a minimum of one isoform was observed with other carbon sources. A major beta-glucosidase (Bgl3A) with the apparent molecular weight of similar to 120 kDa, induced by paper mill waste, was purified 19-fold to homogeneity, with a specific activity of 1,796 U/mg. Bgl3A was a monomeric glycoprotein with 29% of neutral carbohydrate content. It showed optimum activity at pH 4.0 and 5.0, optimum temperature at 60 A degrees C, and exhibited a half-life of 1 h at 60 A degrees C. K (m) of Bgl3A was found to be 0.057 mM with p-nitrophenyl beta-d-glucoside and V (max) was 1,920 U/mg. The purified enzyme exhibited glucose tolerance with a K (i) of 1.5 mM. Bgl3A readily hydrolyzed glucosides with beta-linkage. Bgl3A activity was enhanced (156%) by Zn2+ and was not affected by other metal cations and reagents. The supplementation of Bgl3A (5 U/mg) with Trichoderma reesei cellulase complex (5 FPU/mg) resulted in about 70% of enhanced glucose production, which emphasizes the industrial importance of Bgl3A.
Keywords: beta-Glucosidase; Paper mill waste; Penicillium funiculosum NCL1; Purification; Thermostability

Purification and biochemical characterization of endoglucanase from Penicillium pinophilum MS 20 - Pol, Dipali; Laxman, Ryali Seeta; Rao, Mala (Indian Journal of Biochemistry & Biophysics, 2012)
Cellulases find increasing prominence in sustainable production of fuel and feedstock from lignocellulosic biomass. The purification and biochemical characterization of individual components of cellulase complex is important to understand the mechanism of their action for the solubilization of crystalline cellulose. In this study, an extra-cellular endoglucanase isolated from culture filtrate of Penicillium pinophilum MS 20 was purified to homogeneity by ammonium sulphate precipitation, ion-exchange chromatography and gel filtration. The purified endoglucanase (specific activity 69 U/mg) was a monomeric protein with molecular mass of 42 kDa, as determined by SDS-PAGE. The endoglucanase was active over a broad range of pH (4-7) with maximum activity at pH 5 and showed optimum temperature of 50 degrees C. It retained 100% activity at 50 degrees C for 6 h and half- lives of 4 h and 3 h at 60 degrees C and 70 degrees C, respectively. The kinetic constants for the endoglucanase determined with carboxymethyl cellulose as substrate were V-max of 72.5 U/mg and apparent K-m of 4.8 mg/ml. The enzyme also showed moderate activity towards H3PO4 swollen cellulose and p-nitrophenyl beta-D-glucoside, but no activity towards filter paper, Avicel and oat spelt xylan. The activity was positively modulated by 47, 32 and 25% in the presence of Co2+, Zn2+ and Mg2+, respectively to the reaction mixture. The wide pH stability (4-7) and temperature stability up to 50 degrees C of endoglucanase makes the enzyme suitable for use in cellulose saccharification at moderate temperature and pH.
Keywords: Biochemical properties; Carboxymethyl cellulose; Endoglucanase; Penicillium pinophilum MS 20; Purification

Slow-tight binding inhibition of pepsin by an aspartic protease inhibitor from streptomyces sp MBR04 - Menon, Vishnu; Rao, Mala (International Journal of Biological Macromolecules, 2012)
The present article reports a low molecular weight aspartic protease inhibitor from a Streptomyces sp. MBR04 exhibiting a two-step inhibition mechanism against pepsin. The kinetic interactions revealed a reversible, competitive, slow-tight binding inhibition with an IC50 and K-i values of 4.5 nM and 4 nM respectively. The conformational changes induced upon inhibitor binding to pepsin was monitored by far and near UV analysis, demonstrated that the inhibitor binds to the active site and causes inactivation. Chemical modification of the inhibitor with WRK and TNBS abolished the antiproteolytic activity of the inhibitor. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Aspartic protease inhibitor; Low molecular weight; Slow-tight binding inhibition

Trends in bioconversion of lignocellulose: biofuels, platform chemicals & biorefinery concept - Menon, Vishnu; Rao, Mala (Progress in Energy and Combustion Science, 2012)
Bioconversion of renewable lignocellulosic biomass to biofuel and value added products are globally gaining significant prominence. Market forces demonstrate a drive towards products benign to natural environment increasing the importance of renewable materials. The development of second generation bioethanol from lignocellulosic biomass serves many advantages from both energy and environmental point of views. Biomass an inexpensive feedstock considered sustainable and renewable, is an option with the potential to replace a wide diversity of fossil based products within the energy sector; heat, power, fuels, materials and chemicals. Lignocellulose is a major structural component of woody and non-woody plants and consists of cellulose, hemicellulose and lignin. The effective utilization of all the three components would play a significant role in the economic viability of cellulosic ethanol. Biomass conversion process involves five major steps, choice of suitable biomass, effective pretreatment, production of saccharolytic enzymes-cellulases and hemicellulases, fermentation of hexoses and pentoses and downstream processing. Within the context of production of fuels from biomass, pretreatment has come to denote processes by which cellulosic biomass is made amenable to the action of hydrolytic enzymes. The limited effectiveness of current enzymatic process on lignocellulose is thought to be due to the relative difficulties in pretreating the feedstocks. The present review is a comprehensive state of the art describing the advancement in recent pretreaments, metabolic engineering approaches with special emphasis on the latest developments in consolidated biomass processing, current global scenario of bioethanol pilot plants and biorefinery concept for the production of biofuels and bioproducts. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Consolidated biomass processing; Lifecycle assessment; Lignocellulose; Pre-treatment; Saccharifying enzymes; Value-added products

Approach towards biocatalytic valorisation of barley beta-glucan for bioethanol production using 1,3-1,4 beta-glucanase and thermotolerant yeast - Divate, Rupesh; Menon, Vishnu; Rao, Mala (International Biodeterioration & Biodegradation, 2013)
The exploitation of renewable resource containing polymers other than cellulose and hemicellulose are critically important for the feasibility of biofuel production. The potential of 1,3-1,4 glucan 4-gluconohydrolyase mediated saccharification of barley beta-glucan (BG) was investigated for ethanol production using thermotolerant Saccharomyces sp. A maximum hydrolysis of 71% was obtained in 24 h using in-house produced 1,3-1,4 beta-glucanase from an alkalothermophilic Thermomonospora sp. whereas the hydrolysis was 100% with Accellerase (TM) 1000. The synergistic effect of beta-glucosidase and 1,3-1,4 beta-glucanase was demonstrated by the exogenous addition of beta-glucosidase to Thermomonospora 1,3-1,4 beta-glucanase which resulted in complete hydrolysis of BG. The hydrolysates of BG obtained using Accellerase or a cocktail of Thermomonospora 1,3-1,4 beta-glucanase and beta-glucosidase when fermented with free cells of Saccharomyces at 40 degrees C produced an ethanol yield of 0.44 g g(-1) and 0.46 g g(-1) respectively and when fermented with immobilized cells produced a yield of 0.49 g g(-1). The Ca-alginate immobilized yeast cells were reused nine times at 40 degrees C with 100% fermentation efficiency. The economics of barley-to-fuel ethanol program will ameliorate if in addition to barley starch, beta-glucan is also utilized. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-1; 4 Glucan 4-gluconohydrolyase; Barley beta-glucan; Ethanol; Hydrolysis; Synergism; Thermotolerant yeast

Mechanistic insights into the inhibition of endo-beta 1,4 xyloglucan hydrolase by a classical aspartic protease inhibitor - Menon, Vishnu; Rao, Mala (Journal of Fluorescence, 2013)
This is the first report of inactivation of xyloglucanase from Thermomonospora sp by pepstatin A, a specific inhibitor towards aspartic proteases. The steady state kinetics revealed a reversible, competitive, two-step inhibition mechanism with IC (50) and K (i) values of 3.5 +/- 0.5 mu M and 1.25 +/- 0.5 mu M respectively. The rate constants determined for the isomerization of EI to EI* and the dissociation of EI* were 14.5 +/- 1.5 x 10(-5) s(-1) and 2.85 +/- 1.2 x 10(-8) s(-1) respectively, whereas the overall inhibition constant K (i) (*) was 27 +/- 1 nM. The conformational changes induced upon inhibitor binding to xyloglucanase were monitored by fluorescence analysis and the rate constants derived were in agreement with the kinetic data. The abolished isoindole fluorescence of o-phthalaldehyde (OPTA)-labeled xyloglucanase and far UV analysis suggested that pepstatin binds to the active site of the enzyme. Our results revealed that the inactivation of xyloglucanase is due to the interference in the electronic microenvironment and disruption of the hydrogen-bonding network between the essential histidine and other residues involved in catalysis.
Keywords: 4 xyloglucan hydrolase; Endo-beta 1; Enzyme kinetics; Inactivation mechanism; Pepstatin; Slow-tight binding

Interactions of a low molecular weight inhibitor from streptomyces sp. MBR04 with human cathepsin D: implications in mechanism of inactivation - Menon, Vishnu; Rao, Mala (Applied Biochemistry and Biotechnology, 2014)
Cathepsin D, a lysosomal aspartic protease, is of potential interest as a target for drug design due to its implication in breast and ovarian cancer. The article reports a low molecular weight cathepsin D inhibitor from Streptomyces sp. MBR04. The M-r of the inhibitor was 1,078 Da as determined by MALDI-TOF, and the amino acid analysis showed the presence of Asp, Asp, Gly, Ala, Lys, Leu, Tyr, Trp residues. The steady-state kinetic interactions revealed reversible, competitive, slow-tight-binding nature of the inhibitor with an IC50 and K (i) values of 3.2 and 2.5 nM, respectively. The binding of the inhibitor with the enzyme and the subsequent conformational changes were monitored by exploiting the intrinsic fluorescence of the surface exposed Trp-54 residue. Based on the fluorescence and circular dichroism studies, we demonstrate that the inhibitor binds to the active site of cathepsin D and causes inactivation. All these kinetic, thermodynamic, and quenching studies suggest that the newly isolated peptidic inhibitor could be a potential scaffold to study and can be used to develop new potent therapeutic lead molecule for the development of drugs. The inhibitor will be significant as a potential lead molecule to target cathepsin D.
Keywords: Cancer treatment; Cathepsin D inhibitor; Inactivation mechanism; Slow-tight-binding inhibition; Streptomyces sp MBR04

Dr. V. Jagannathan (1921-2015) Obituary - Rao, Mala; Deshpande, Vasanti; Ingle, Prabhakar (National Academy Science Letters-India, 2016)